The Fatimids and the First Crusade (Journal of the College of Basic Education, 2022)
In this research, I dealt with the position of the Fatimids on the first Crusade, and how their position was towards it at the beginning of the events, and their lack of knowledge of what the Crusades were at the beginning of their arrival, trying to benefit from them, and their movement towards Palestine and its areas of influence, and they did not initiate contact with the Seljuks, just as the Seljuks did not move to cooperate with the Fatimids, and how the events led after that To a catastrophe that befell the region that lasted two centuries, and if they were destined and united to spare the region all these calamities, the research was divided into two sections.